Cover Image. Issue 7 (8th June 2017) - Patel, A.; Cassell, B.; Sainani, N.; Wang, D.; Shahid, B.; Bennett, M.; Mirza, F. A.; Munigala, S.; Gyawali, C. P.
Abstract : The cover image, by A. Patel et al., is based on the Original Article Comparison of motor diagnoses by Chicago Classification versions 2.0 and 3.0 on esophageal high‐resolution manometry, DOI10.1111/nmo.13042 .